2008
DOI: 10.1097/ico.0b013e3181658408
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Corneal Cells and Nerves in an Implanted Collagen Corneal Substitute

Abstract: We show that a simple ECM mimetic can promote regeneration of corneal cells and nerves. Gradual turnover of matrix material as part of the natural remodeling process allowed for stable integration with host tissue and restoration of mechanical properties of the organ. The simplicity in fabrication and shown functionality shows potential for ECM substitutes in future clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…First, the ECM acts as a biological scaffold that provides the appropriate microenvironment for corneal repair and regeneration during wound healing. 16 Second, the ECM, composed mainly of collagen and representing >70% of the dry weight of the cornea, is essential for corneal transparency because of the regular arrangement of uniformly thin collagen fibrils into lamellae. 17,18 Therefore, much effort has been expanded to develop efficient ECM for tissue-engineered corneal equivalents, although none has been clinically usable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the ECM acts as a biological scaffold that provides the appropriate microenvironment for corneal repair and regeneration during wound healing. 16 Second, the ECM, composed mainly of collagen and representing >70% of the dry weight of the cornea, is essential for corneal transparency because of the regular arrangement of uniformly thin collagen fibrils into lamellae. 17,18 Therefore, much effort has been expanded to develop efficient ECM for tissue-engineered corneal equivalents, although none has been clinically usable.…”
Section: Discussionmentioning
confidence: 99%
“…Recellularization of a decellularized graft is important because keratocytes play an active role in the maintenance and metabolism of the corneal stroma. 16,22,23 In addition, this decellularized porcine corneal stroma could be used as a matrix for culturing human corneal cells in vitro and making a tissue-engineered cornea.…”
Section: Figmentioning
confidence: 99%
“…Researchers reported no difference between type I and III collagen‐based substitutes with both being nerve‐friendly. These substitutes, following further clinical testing, show promise in helping to alleviate the shortage of corneal material and as emergency patch grafts 53–55 …”
Section: Emerging Devicesmentioning
confidence: 99%
“…Previous experiments using collagen only scaffolds for corneal applications have demonstrated that EDC:NHS collagen hydrogels have an excellent microstructure to foster cell growth . The addition of both CNTs and chitosan to the collagen matrix prior to cross‐linking was shown not to have a significant impact on the microstructure of the hydrogel (Figure b).…”
Section: Resultsmentioning
confidence: 90%